Tax Wedge and Its Impact on Employment in OECD Countries - Radu, Claudia Florina; Schebesch , Klaus Bruno; Fenișer , Cristina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2025)
Our study explores the relationship between the tax wedge, unemployment rate and employment rate on the labor market in a comparative framework, highlighting existing approaches in the OECD countries. There are considerable differences in the level of the tax wedge between the OECD countries. The relationship between the tax wedge, employment rate and unemployment rate is a complex one, involving a broad approach, but appropriate to the particularities of each country. Such a comparative analysis at the level of the OECD countries offers us interesting perspectives, in order to adjust the policies that aim, on the one hand, to ensure budget revenues and, on the other hand, to stimulate economic growth and support employment. In order to identify the link between them, we used hierarchical cluster analysis, for a sample of 37 OECD countries. After analyzing the data from the OECD countries, we concluded that there is a positive correlation between the level of the tax wedge and the unemployment rate. Thus, in countries where the tax wedge is higher, the unemployment rate tends to be higher and vice versa. But this is verified especially for cluster 2, which includes Romania and most of the countries in Central-Eastern Europe. Therefore, it is particularly important to adopt those fiscal measures that stimulate employment and have beneficial effects on the results of the labor market. The associated new data modeling contributes to filling a gap in the statistical analysis of tax wedge implications by using a combination of quantile regression and clustering, finding robust country subgroups that enable refined, context-sensitive policy recommendations.